(untitled) (Damascus University Journal of agriculture sciences, 2025)
This study aimed to isolate the smut pathogens from infected sorghum plants in our region, define them, and test their ability to infect several genotypes (varieties) of sweet sorghum and a local cultivar, Razineah 17, also broom corn plants in field. The study showed that sorghum infected by 4 smut fungus, they are covered kernel smut B, head smut A, loose smut S, and long smut L. Based on pathogenicity results in field, (varieties, genotypes) of sweet sorghum did not show any symptoms of covered kernel smut, head smut or loose smut, on the other hand, plants of broom corn and Razineah 17 were infected during the study seasons with covered kernel smut only, while broom corn susceptibility was tested only during the 2017 and 2018. Results showed unsignificant differences among broom corn and Razineah 17 for disease incidence and severity under fields conditions. Field tests also showed an increase in infection rate and severity when the inoculation rate increased.